Increasing the Students' Reading Comprehension Ability in Descriptive Text Through Discovery Learning at The Eighth Grade of SMP Negeri 2 Gido in 2022/2023 - Derita Gulo; Yasminar Amaerita Telaumbanua; Yaredi Waruwu; Hidayati Daeli (Departement of Mathematics Education, 2023)
Students are expected to comprehend English texts correctly. Meanwhile the students of the eighth grade of SMP Negeri 2 Gido did not understand the texts, could not achieve the minimum competences criterion that has been decided in the school. It was caused by some factors namely lacked of the students’ vocabulary, unable to identify main idea and to determine the generic structure of descriptive text, lacked of getting the important points when reading the text. The purpose of this research is to increase the students’ ability in reading comprehension. In increasing students’ reading ability, the researchers used Discovery Learning Strategy and applied it Classroom Action Research (CAR). This research was conducted in two cycles, there were four steps in conducting the research, namely: planning, action, observation and reflection. The result of the data in Cycle I showed that there were 2 students (6%) categorized in “Poor level”, 12 students (37%) categorized in “Less level”, 14 students (42%) categorized in “Enough level, 3 students (9%) categorized in “Good level, and 2 students (6%) categorized in “Very good level”. The mean mark in Cycle I was 50.91. There were still many students who failed and their level was low and really needed to be increased in the next cycle. Cycle II, no one of the students was categorized into less, poor, and enough levels, but 30 students (90.9%) categorized in “Good level, 3 students (9.10%) categorized in “Very good level”. The mean mark in Cycle II was 85.15. Based on the results of the research, it is concluded that Discovery Learning Strategy can increase the students’ ability in reading comprehension in descriptive text at eighth grade of SMP Negeri 2 Gido in 2022/2023.